Identity-based SIP Authentication and Key Agreement - Wu ShaoBo; Li ChengShu (2011 Seventh International Conference on Computational Intelligence and Security, 2011)
The Session Initiation Protocol (SIP) is designed by taking the establishment of IP telephone network on Internet as the starting point, which has brought new vitality for the IP telephone services. SIP has faced a lot of security threats due to its own characteristics and the application environment. The vulnerability of SIP has been firstly analyzed in this paper. At the same time, based on the theory of identity authentication public key system, a scheme of SIP authentication and key agreement based on identity authentication has been also proposed in this paper. The structure is simple and the application is easy, which has greatly simplified the certificate management and maintenance as well as effectively improved the safety performance of SIP.